2021
DOI: 10.3390/app11030988
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Skinsuit Zigzag Tape Turbulators on Speed Skating Performance

Abstract: At the 1998 Nagano Winter Olympic Games, zigzag tape was introduced on the race suit lower legs and cap of speed skaters. Application of these zigzag devices on live skaters and cylinders in the wind tunnel showed large improvements in the aerodynamic drag. These wind-tunnel results were unfortunately not widely published, and the impact of the zigzag strips in a real skating environment was never established. This paper aims to show the background of the application of the zigzag tape and to establish the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies have shown that for every 1 • decrease in the push-off angle, speed increases by 0.011 m/s [11]. In speed skating at a speed above 60 km/h [12], the difference between first and second place often lies between 0.01 and 0.02 s [13]. As a result, the change in the push-off angle may have a direct impact on an athlete's performance and their further success in competitions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that for every 1 • decrease in the push-off angle, speed increases by 0.011 m/s [11]. In speed skating at a speed above 60 km/h [12], the difference between first and second place often lies between 0.01 and 0.02 s [13]. As a result, the change in the push-off angle may have a direct impact on an athlete's performance and their further success in competitions.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the measurements made in a wind tunnel are generally very repeatable. Researchers have previously used a simplified cylindrical geometry to evaluate the aerodynamic properties of textile features such as tightness, 12 surface morphology 13,14 and so on. CFD has been extensively used to study the aerodynamic characteristics of cylinders with different surface.…”
Section: Introductionmentioning
confidence: 99%